2013
DOI: 10.1175/jcli-d-12-00862.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the AMOC Variability on the Atmosphere in CCSM3

Abstract: The influence of the Atlantic meridional overturning circulation (AMOC) variability on the atmospheric circulation is investigated in a control simulation of the NCAR Community Climate System Model, version 3 (CCSM3), where the AMOC evolves from an oscillatory regime into a red noise regime. In the latter, an AMOC intensification is followed during winter by a positive North Atlantic Oscillation (NAO). The atmospheric response is robust and controlled by AMOC-driven SST anomalies, which shift the heat release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 43 publications
6
34
1
Order By: Relevance
“…As the AMOC intensification is driven by the positive NAO in the first place, this implies a weak positive feedback between the AMOC and the NAO, which would enhance the low-frequency power of the ocean-only mode suggested by Kwon and Frankignoul (2012). In regime 1, Frankignoul et al (2013) found no direct evidence of AMOC influence on the atmosphere. However, upper ocean heat content anomalies resembling the AMOC footprint were found to precede the negative NAO, albeit lacking robustness, which hints at a weak negative feedback that should contribute to the oscillatory character of regime 1.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…As the AMOC intensification is driven by the positive NAO in the first place, this implies a weak positive feedback between the AMOC and the NAO, which would enhance the low-frequency power of the ocean-only mode suggested by Kwon and Frankignoul (2012). In regime 1, Frankignoul et al (2013) found no direct evidence of AMOC influence on the atmosphere. However, upper ocean heat content anomalies resembling the AMOC footprint were found to precede the negative NAO, albeit lacking robustness, which hints at a weak negative feedback that should contribute to the oscillatory character of regime 1.…”
Section: Introductionmentioning
confidence: 91%
“…The basic features of the North Atlantic ocean circulation in CCSM3 have been presented in Danabasoglu (2008), Kwon and Frankignoul (2012), Tulloch and Marshall (2012), and Frankignoul et al (2013). Here we briefly discuss the mean fields in regime 1.…”
Section: Mean Amoc Streamfunctions In Depth and Density Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a response of the North Atlantic Oscillation (NAO) to North Atlantic SSTs has been found both in observations and model studies Frankignoul, 1999, 2002;Rodwell and Folland, 2002;Frankignoul et al, 2013;Gastineau et al, 2013;Gastineau and Frankignoul, 2015). Via the Atlantic Multidecadal Oscillation (AMO), which is thought to be associated with AMOC and OHT variability (e.g.…”
Section: Introductionmentioning
confidence: 98%